Populism and democratic crisis in semi-presidential countries. Issue 8 (17th November 2019) - Tsai, Jung-Hsiang
ABSTRACT: This article demonstrates how different political opportunity structures in semi-presidential countries either enable or inhibit the overreach of populist presidents. In Turkey, for example, political leverage has been used to hamstring the opposition and transform a democratic regime into an authoritarian one. In Bulgaria, democracy also faded under a populist prime minister. Ukraine's democracy had a checkered history, with frequent changes of power culminating in presidential breakdown. The Czech Republic introduced popular elections for the president to strengthen legitimacy, but that exposed the regime to conflict between the president and the prime minister.